Clothed particle representation in quantum field theory: mass renormalization - Korda, V.Yu.; Shebeko, A.V. (Вопросы атомной науки и техники, 2007)
The method of unitary clothing transformations is applied in the model involving nucleon and neutral pion fields interacting via the regularized pseudoscalar Yukawa-type coupling. In this approach the mass counterterms are cancelled (at least, partly) by commutators of the generators of clothing transformations and the field interaction operator forming the pion and nucleon mass shifts expressed through the corresponding three-dimensional integrals whose integrands depend on certain covariant combinations of the relevant three-momenta. The property provides the momentum independence of mass renormalization. The conditions imposed upon the cutoff vertex function are specified. Метод унітарних одягаючих перетворень застосовано в моделі квантової теорії поля, в якій нуклонне і нейтральне піонне поля взаємодіють через регуляризований зв’язок типу Юкави. В цьому підході масові контрчлени частково скорочуються з комутаторами генераторів одягаючих перетворень і операторів взаємодії, що формує піонні та нуклонні зсуви мас. Знайдені величини подаються тривимірними інтегралами від деяких коваріантних комбінацій відповідних імпульсів частинок, що забезпечує незалежність розрахованих поправок від імпульсів. Визначено умови, що висуваються до вершинних функцій, які здійснюють регуляризацію зв’язку полів. Метод унитарных одевающих преобразований применен в модели квантовой теории поля, в которой нуклонное и нейтральное пионное поля взаимодействуют посредством регуляризованной псевдоскалярной связи типа Юкавы. В этом подходе массовые контрчлены частично сокращаются с коммутаторами генераторов одевающих преобразований и операторов взаимодействия, формируя пионные и нуклонные сдвиги массы. Найденные величины выражаются трехмерными интегралами от некоторых ковариантных комбинаций соответствующих импульсов частиц, что обеспечивает независимость рассчитанных поправок от импульсов. Определены условия, налагаемые на обрезающие вершинные функции, осуществляющие регуляризацию связи полей.